2020
DOI: 10.1021/acsabm.0c00679
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Dip-Coating-Fabricated Core–Shell Silk Fibroin Rice Paper Fibrous Scaffolds for 3D Tumor Spheroid Formation

Abstract: Bioscaffolds are important substrates for supporting threedimensional (3D) cell cultures. Silk fibroin (SF) is an attractive biomaterial in tissue engineering because of its good biocompatibility and mechanical properties. Electrospinning is one of the most often used approaches to fabricate SF fibrous scaffolds; yet, this technique still faces many challenges, such as low yield, residual organic solvents, limited extensibility of fibers, and a lack of spatial control over pore size. To circumvent these limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…By the Cassie-Baxter state, the air trapped of the micro/nanostructured surface can improve the hydrophobicity and corrosion resistance of Mg/P/Z/F/H materials. [40,41] The Mg/P/Z/F/H materials had the best corrosion resistance and the corrosion rate of Mg/P/Z/F/H was 1.9152×10 -3 mm/y. Here we found that with the addition of ZnO the corrosion resistance of…”
Section: Surface Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…By the Cassie-Baxter state, the air trapped of the micro/nanostructured surface can improve the hydrophobicity and corrosion resistance of Mg/P/Z/F/H materials. [40,41] The Mg/P/Z/F/H materials had the best corrosion resistance and the corrosion rate of Mg/P/Z/F/H was 1.9152×10 -3 mm/y. Here we found that with the addition of ZnO the corrosion resistance of…”
Section: Surface Characteristicsmentioning
confidence: 98%
“…As a widely applied and simple surface treatment technology, dip-coating can produce a relatively adherent, stable and uniform films on the surface of materials. [39][40][41][42] Using dip-coating method the rough Mg/P/Z/F/H structure was constructed, which can be prepared simply and protect the magnesium alloy better. Furthermore, 30minutes' heating process at 50 o C can not only repair defects of the composite Mg/P/Z/F materials' surface but also rearrange the PCL and PFDTES molecules to make the composite surface from hydrophobic (96.5 o ) to superhydrophobic (159.0 o ).…”
Section: Introductionmentioning
confidence: 99%
“…[34]. Copyright 2019, American Chemical Society; Reprinted with permission from [35]. Copyright 2020, American Chemical Society.…”
Section: Porous Scaffoldmentioning
confidence: 99%
“…Some researchers reported a self-assembling peptide, bQ13, that can be useful for obtaining the 3D culture of prostate cancer cells [36]. These self-assembled peptides have been known to help stabilize 3D culture and provide Copyright 2019, American Chemical Society; Reprinted with permission from [35]. Copyright 2020, American Chemical Society.…”
Section: Gel-based Scaffoldsmentioning
confidence: 99%
“…Normally, these systems do not present a good integration between cells and the polymer matrix, and their efficacy for tissue regeneration depends on the physical properties of the polymer matrix such as hydrophobicity, degradation rate, or stiffness [14,27]. Among the most used techniques, we can highlight layer-by-layer [28,29], melt molding [30], photolithography [31], and self-assembling [32].…”
Section: Introductionmentioning
confidence: 99%